Enhancing the defense application with ANSYS model of thermoelectric generation for coil gun. (December 2022) - Sreekala, P.; Ramkumar, A.; Rajesh, K.
Abstract: The concept and functioning of coil guns were investigated after soldiers used reusable and multipurpose rounds in their rifles during combat. Traditional firearms use gunpowder, which limits the gun's use to a single function and quickly depletes the ammo supply. The coil gun, which uses electrical energy harvested from a Bio-thermal energy harvester, allows multifunctional bullets to be used in a rifle during an emergency without exploding. As coil cannon projectiles, deflected bullets or bullet shells from the battlefield can be used if necessary. This means that energy collecting and conversion for autonomous and flexible wearable technologies, as well as other applications like Internet of Things (IoTs), military, industrial, consumer and non-consumer domains, will become an extensively explored topic. Nowadays, energy independence is a hot concern thanks to flexible gadgets' rising popularity. Thermoelectric energy harvesting, a potential new method to gather easily accessible body heat, is particularly well-suited to the wearing of sensors and electronics. A coil gun battery can be charged using a thermoelectric generator (TEG), which can harness energy from the human body. The thermoelectric generator and charger can both be found in a single patch that can be worn. The TEG ANSYS model is used in this research project. Human body heat can be used to power highly specialized applications like medical ones since it is reliable and natural. The average human body produces roughly 100 W of heat while at rest, and about 525 W of heat while exercising.